SEED PRODUCTIVITY AND LEAF ANATOMY OF ASTILBOIDES TABULARIS (HEMSL.) ENGL. - TATIANA NIKOLAEVNA BELYAEVA,; ALINA NIKOLAEVNA BUTENKOVA, (International Journal of Pharma and Bio Sciences, 2016)
This article contains data about seed productivity and leaf anatomy of Astilboides tabularis. The findings show that the plants growing in the southern taiga subzone of Western Siberia (Russia) have a high rate of real seed productivity and seed germination in the light. The leaf anatomy of Astilboides tabularis has allowed the plant to be relegated as a mesophyte. The plants can be used as distinctive ornamental plants for landscaping, partially shaded and shaded habitats, especially landscape compositions in natural style.